ROLE OF SPIRITUALITY IN THE VUCA WORLD AND ITS IMPACT ON CORPORATE GOVERNANCE - et al., Anu Pandey (International Journal of Advanced Science and Technology, 2019)
Today’s business environment is highly dynamic. With so much volatility and uncertainty there is bound to be stress, cut throat competition and worry. People working in such an environment are focusing on making material gains. Making profits by hook or crook has become the latest mantra. Business ethics and morality have taken a backseat. This race for becoming number one has negatively impacted the health of the employees. There has been a rise in the cases of heart attacks, blood pressure, depression etc. To counter this problem many companies have taken to the path of spirituality. India is a hub of spiritual leaders and there are organizations like Isha foundation. Brahmakumaris, Art of Living, Vipassana etc. who have been approached by the corporates to conduct spiritual classes for their employees. This has not only positively impacted the employees but also affected their corporate governance. This paper is an endeavor to study the linkages between the corporates and the spiritual organizations and their impact on corporate governance.